2002
DOI: 10.1128/aem.68.12.5870-5876.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection by PCR-Enzyme-Linked Immunosorbent Assay ofClostridium botulinumin Fish and Environmental Samples from a Coastal Area in Northern France

Abstract: The prevalence of Clostridium botulinum types A, B, E, and F was determined in 214 fresh fish and environmental samples collected in Northern France. A newly developed PCR-enzyme-linked immunosorbent assay (ELISA) used in this survey detected more than 80% of samples inoculated with fewer than 10 C. botulinum spores per 25 g and 100% of samples inoculated with more than 30 C. botulinum spores per 25 g. The percent agreement between PCR-ELISA and mouse bioassay was 88.9%, and PCR-ELISA detected more positive sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 40 publications
0
54
1
1
Order By: Relevance
“…Fish are suspected of harboring the bacteria in their gastrointestinal tracts, where toxin is subsequently formed, perhaps under certain stressful conditions. In the past, detection of Clostridium botulinum within an animal has involved inoculation of growth media with tissue, intestinal contents, or fecal material, followed by DNA extraction of the media and finally polymerase chain reaction (Szabo et al, 1994;Hielm et al, 1996Hielm et al, , 1998Kimura et al, 2001;Fach et al, 2002). This method of sample preparation does not distinguish between spores, the resting phase, and cells, the active phase of the organism.…”
mentioning
confidence: 99%
“…Fish are suspected of harboring the bacteria in their gastrointestinal tracts, where toxin is subsequently formed, perhaps under certain stressful conditions. In the past, detection of Clostridium botulinum within an animal has involved inoculation of growth media with tissue, intestinal contents, or fecal material, followed by DNA extraction of the media and finally polymerase chain reaction (Szabo et al, 1994;Hielm et al, 1996Hielm et al, , 1998Kimura et al, 2001;Fach et al, 2002). This method of sample preparation does not distinguish between spores, the resting phase, and cells, the active phase of the organism.…”
mentioning
confidence: 99%
“…This finding links tilapia to the deaths of pelicans and other piscivorous birds by type C avian botulism at Salton Sea. To our knowledge, this association has not been demonstrated in any other bird or fish population, although similar work has looked for other types of C. botulinum (Fach et al, 2002). The intestines of healthy fish generally would be considered inhospitable to C. botulinum, but Riedel and Costa-Pierce (2001) showed that Salton Sea tilapia consume significant amounts of sediment during the year.…”
Section: Discussionmentioning
confidence: 93%
“…Generally, the data connected with detection of C and D C. botulinum types with PCR based method is rarely presented in the literature. An extensive part of the available literature concerns the occurrence of this microorganism in food, faecal, and environmental samples (6,8,15,18). Furthermore, the scale of C. botulinum and especially the occurrence of C and D types in feed is underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect could be caused by natural microflora, such as: other Clostridium strains, which reveal faster growth (C. perfringens, C. tetani), Staphylococcus, and Bacillus. Moreover, the PCR amplification could be affected by heavy metals occurring in inoculated silage samples (6,8,15,20). The inhibitory effect of matrix ingredients was also described by other authors who detected C. botulinum in different types of samples.…”
Section: Discussionmentioning
confidence: 99%